Analisis Kematangan Karir dalam Keputusan Karir: Studi Kasus pada Siswa Kelas XII SMA N Ngabang - Febriani, Lina Dwi; Astuti, Indri; Afandi, Afandi (JURNAL KONSELING GUSJIGANG, 2023)
Career maturity is the direction of development and career expectations desired by students. This survey research aims to determine the level of career maturity of class XII students in career decisions. This research was conducted on 279 class XII students in Ngabang sub-district. The instrument in this study used a CDSE-SF questionnaire (Betz Karen, 2012). This questionnaire consists of five indicators and each indicator has 5 statement items. The results showed that the indicators for self-assessment were moderate, indicators for job information were high, indicators for selecting goals were moderate, indicators for planning were low, indicators for problem solving were moderate and in general, the maturity level of career decisions for grade XII students was at a moderate level 57%. Thus the results of this study will provide meaningful results and can be used as a reference for BK teachers and stakeholders to prepare for better career maturity. Suggestions for further research are very important for all XII graders with a larger sample size, so that the results will be more comprehensive.